(untitled) (Experimental biology, 2019)
Soybean varieties, resistant to various stresses, and especially varieties resistant to drought, are required for a wide variety of soil and climatic conditions of Kazakhstan. A necessary condition for effective selection for drought resistance is the correct assessment of drought resistance. Together with the assessment of seed yield in drought, the use of physiological, anatomical, morphological and biochemical traits of drought resistance allows to conduct more comprehensive assessment. The targeted use of phe-notypic markers will allow the breeders to select valuable soybean genotypes from the collection, which can be used in various crossbreeding schemes to develop productive and drought-resistant forms. In this article, soybean collections were assessed using anatomic-morphological and physiological-biochemical methods for the drought tolerance assessment by contrasting conditions of irrigation and noirrigated in scientific field station of KazSRIA&PG during the phase of bean filling and striking manifestations of moisture deficiency. Samples were identified according to high pubescence, well-developed stomatal apparatus, intensive proline accumulation, elevated level of the quantum yield of the photosystem (QY). 3 varieties such as Gessenska, Kye-Shuang, Comet were identified as drought-resistant types by two and three phenotypic markers of drought resistance. The possibility of using a modern fluorometer to assess the physiological state of plants during periods of stress caused by drought was demonstrated. The samples selected as drought-resistant will be used in hybridization to develop valuable hybrid populations and further domestic drought-resistant varieties adapted to conditions non-irrigated agriculture of Kazakhstan. Key words: soybean, drought tolerance, trait, xeromorphism, pubescence, free proline, stomata, quantum yield of the photosystem.